Social Media-Based Collaborative Learning Effects on Student Performance/Learner Performance With Moderating Role of Academic Self-Efficacy - Liu, Shuai; Zaigham, Ghulam Hussain Khan; Rashid, Rao Muhammad; Bilal, Ahmad (Frontiers in Psychology, 2022)
Social media has been always described as the channel through which knowledge is transmitted between communities, students and learners. This social media has been utilized by university students in a way to encourage collaborative learning and social interaction. This study explores the use of social media in the process of collaborative learning among university students in China using survey method, a total 583 students of different universities has surveyed in this study. Through this investigation, different factors enhancing collaborative learning in among university students in the context of using social media are going to be examined. The structural equation modeling (SEM) and hierarchical regression was used to analyze the suggested hypothesis. Results shown that perceived benefit, active learning, and interaction with students is significantly related to social media collaborative. However, perceived ease of use and perceived usefulness has insignificant effect in social media collaborative learning. Additionally, students’ academic self-efficacy significantly moderate the relationship between social media collaborative and learning performance. The implication, and limitation of the study also discussed in the last section.